On-line Monitoring System of Capacitive Equipment Dielectric Loss - Xin-bo Huang; Tu Deng; Jie Shi (Institute of Advanced Engineering and Science, 2014)
To ensure capacitive equipment working safely and reliably, an on-line monitoring system of capacitive equipment dielectric loss was developed. The insulation situation was estimated accurately through long-distance synchronous sampling (using IRIG-B code synchronous clock), seamless connection of data between devices using Intelligent Electronic Device (IED), communication following IEC61850 protocol, and data analysis (using fault diagnosis algorithm). Running results showed that the system not only can accurately monitor the information, such as leakage current, dielectric loss, and equivalent capacitance, which reflect the working condition of capacitive equipment, but also can transmit data to the on-line monitoring data center through the IEC61850 protocol. The operating data, monitoring on CVTs in 330kV substation, showed the great improvement of this system on credibility, accuracy, and stability. What’s more, it also proved the great value of using and promoting this system. DOI : http://dx.doi.org/10.11591/telkomnika.v12i6.4866